HOW LONG CAN THE HUNGARIAN AUTHORITARIAN REGIME SURVIVE? - Roland A. Csizmazia (PEOPLE: International Journal of Social Sciences, 2026)
This political analysis examines the rise and fall of Viktor Orbán's authoritarian regime in Hungary (2010-2026), addressing the fundamental question: what limits the survival of electoral autocracies? Over sixteen years, Orbán consolidated power through systematic institutional manipulation — rigging electoral systems, increased control over media, rewriting constitutions, and dismantling checks and balances — while maintaining the facade of democratic legitimacy. Despite the remarkable durability of these mechanisms, the regime ultimately collapsed in April 2026 under the weight of compounding crises: a corruption-plagued economy (25% inflation, 0.4% growth), the clemency scandal of February 2024 that destroyed core credibility, severe international isolation due to the intensified friendly policy towards Russia and China, and €13 billion in frozen EU funds. Part of the old opposition saw the chance to unify behind Péter Magyar, who has served the regime during for fourteen years. As an insider he weaponized his insider knowledge against his former peers. Hungary's case clearly demonstrates that electoral autocracies are stable as long as the economy allows it; they require constant institutional balancing that eventually breaks under compounding pressures.